Acts of decolonial love in academic literacy: practitioners’ perspectives and transformative practices - Sibanda, Brian (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
The concept of decolonial love offers a transformative alternative lens for re-imagining and re-thinking the teaching and learning of academic literacy in South African higher education. Decolonial love challenges deficit-based, Eurocentric models and foregrounds students’ sensibilities, bodies, cultural repertoires, knowledges and lived experiences by insisting on affirmation, recognition, and respect for humanity in its totality. This study examines how academic literacy practitioners enact non‑violent epistemic practices to create cracks in colonial pedagogies and practices and affirm alternative epistemologies. Employing a qualitative methodology, the study draws on questionnaire data collected from 16 members of the Social Justice Interest Group (SIG) of the South African Association for Academic Literacy Practitioners (SAAALP). The questionnaire comprised open‑ended questions on pedagogical strategies, material selection, technology use, and institutional challenges and support. Findings show that disobedient acts of decolonial love in academic literacy foster inclusive learning environments where students can be different together. Practitioners report that enhanced engagement and critical consciousness when teaching and learning validates students’ identities and experiences, noting that exercises based on Ubuntu pedagogy of care and community engagement cultivate a sense of being and belonging.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 6, Volume 9, 2025
Keywords: Academic literacy; Decolonial love; Decolonial cracks; Ubuntu; Coloniality; Praxis; Academic achievement; Literacy; Literacy -- Social aspects; Education higher, South Africa; Study skills; College student orientation